MODEL BISNIS STARTUP PENDIDIKAN DALAM PERSPEKTIF ISLAM - Yulianto, Harry; Iryani, Iryani; Amrullah, Amiruddin (HUNAFA Jurnal Studia Islamika, 2024)
This study examines the integration of Islamic values in the business model of educational startup in Indonesia and how these values contribute to the sustainability and competitive position of these businesses in a highly competitive market. The issue addressed was the challenge faced by educational startup in balancing profit with social impact while adhering to Islamic principles, such as justice, transparency, and community benefit. The research positions itself as an exploration of how Islamic values can strengthen the business model of educational startup, making them not only financially viable but also socially responsible. The question was discussed by analyzing the operational and strategic implications of applying Islamic ethics in the education sector, with a focus on inclusivity, fairness, and sustainable business practices. Using a qualitative descriptive approach, the paper reviews relevant literature on Islamic business ethics and its application in educational startup. The findings indicate that integrating Islamic values enhances trust, customer loyalty, and long-term sustainability, while offering a unique competitive advantage in the market. The research concludes that adopting Islamic principles in business models offers a viable path for educational startup to create a positive social impact while ensuring business success in the evolving educational landscape.